Uji Aktivitas Anti Bakteri Ekstrak Etanol Daun Pacar Air (Impatiens balsamina L.) terhadap Bakteri Escherichia coli - Hardiana Hardiana; Yuni Dewi Safrida; Rizki Khana Maulianda (Jurnal Serambi Engineering, 2020)
(Impatiens balsamina L.) is an ornamental plant that has been widely developed as a medicinal plant. Secondary metabolites of water henna plant (Impatiens balsamina L.) are known to contain flavonoids. In the field of pharmacology this plant is often used because it has antibacterial agents. This study aimed to determine the inhibitory effect and the optimum antibacterial concentration of the ethanol extract of the leaves of water henna (Impatiens balsamina L.) against the growth of Escherichia coli bacteria with treatment concentrations those are 25%, 50%, 75%, and 100%. This research was conducted at the Akafarma Microbiology Laboratory in Banda Aceh. The method used was experimental with disk diffusion (disc method). The results showed that in repetition I and II with concentrations of 25%, 50 percent, 75 percent, and 100 percent, the zone of inhibition was obtained respectively those are 23 mm, 26 mm, 29.5 mm, and 31 mm. The optimum result of the ethanol extract of Impatiens balsamina L. leaves in inhibiting the growth of Escherichia coli is at the concentration of 100% with an inhibition zone diameter of 31 mm.